تحليل العوامل المنبئة للوفيات عند مرضى التحال الدموي - لايقة, عنان (Latakia University Journal -Medical Sciences Series, 2019)
إن هدف دراستنا كان تحديد العوامل المنبئة للوفاة عند مرضى التحال الدموي في مشفى الأسد الجامعي باللاذقية المقبولين بين عامي /2006- 2009/م آخذين في الحسبان بعض عوامل الخطورة مثل: فقر الدم ,اضطرابات الكالسيوم –الفسفور ,الالتهاب وسوء التغذية . حيث قمنا بمقارنة العوامل السكانية وعوامل الخطورة والمعطيات المخبرية الآتية (االهيموغلوين-الهيماتوكريت-كرياتينين الدم- البولة الدموية- كالسيوم الدم - وفسفور الدم- PTH - ألبومين الدم –CRP ) عند المرضى المتوفين والمرضى الذين ما زالوا على التحال (الأحياء) خلال فترة الدراسة. النتائج: 64 مريضا من بين 136 من مرضى التحال الدموي قد توفوا والسبب الرئيسي للوفاة كانت الحوادث القلبية الوعائية (28%) يليها ارتفاع بوتاسيوم الدم (,512 % ) ثم الإنتان (11%) . المتوفون كانوا أكبر عمرا من الأحياء ولديهم هيموغلوبين الدم وألبومين الدم أقل, بينما كالسيوم الدم وفسفور الدم و CRP أعلى من المرضى الأحياء. هذه المعطيات تفترض أن عوامل فقر الدم والالتهاب وسوء التغذية مهمة في تحديد الوفاة لدى مرضى التحال الدموي. The objective of our study was to determine the predictors of mortality in Hemodialysis patients, considering certain risk factors such as anemia, calcium-phosphate disorders, nutrition-inflammation and treatment/dialysis-related risk factors at Al- Assad University Hospital in Lattakia (2006-2009). Demographic, risks factors, laboratory data (hemoglobin, hematocrit, creatinine, albumin, Ca,P,PTH,CRP) were compared between survivors and nonsurvivors. Sixty-four of the 136 HD patients died during the follow-up period, and the main cause of death was cardiovascular events (28%), followed by hyperkalemia (12.5%), and infection/sepsis (11%). The patients who died were older than those alive, had lower serum levels of hemoglobin (Hb), albumin. Serum levels of calcium, C-reactive protein (CRP) and PTH were higher in patients who died during the follow-up period. These findings suggest that, inflammation, malnutrition, and anemia are important determinant factors of mortality in HD patients.